2019
DOI: 10.1016/j.jfluidstructs.2019.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Morphing of a supercritical wing by means of trailing edge deformation and vibration at high Reynolds numbers: Experimental and numerical investigation

Abstract: This article examines the morphing effects of the trailing-edge deformation and vibration on the turbulent structures in the wake of a supercritical Airbus-320 wing. It is shown that the electroactive morphing has the capacity to produce an enhanced aerodynamic performance (lift increase, drag reduction) and reduce the amplitude of instability modes associated to aerodynamic noise. The appropriate actuation is achieved with piezoactuators placed in the trailing edge region. The work presented has been carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Low turbulence levels mean less tonal noise and vice versa. In a recent study from Yu and Yang [33] it was shown that an oscillating trailing edge fringe is able to reduce the strength and size of the shed vortices, similar as observed for an active oscillation of the trailing edge reported by Simiriotis et al [34]. A flaplets, the short flaplets were also extremely effective at Re c > 600, 000.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Low turbulence levels mean less tonal noise and vice versa. In a recent study from Yu and Yang [33] it was shown that an oscillating trailing edge fringe is able to reduce the strength and size of the shed vortices, similar as observed for an active oscillation of the trailing edge reported by Simiriotis et al [34]. A flaplets, the short flaplets were also extremely effective at Re c > 600, 000.…”
Section: Discussionsupporting
confidence: 73%
“…While the analytical approach was able to determine multiple frequencies that could be reduced, their experimental results revealed only a single zone where the reduction is observed, similar to the results herein. We would like to point out that it cannot be excluded from their experiments that small vibrations existed, especially as the herein observed acoustic effect is already visible for vibration amplitudes as small as 100-200 µm (compare also the study with active oscillating flaplets with a similar effect at similar oscillation amplitudes, see Simiriotis et al [34]). Furthermore, their noise reduction was focusing on the broadband noise while the flaplets herein clearly address the tonal noise components.…”
Section: Discussionmentioning
confidence: 76%
“…They also showed that the lift coefficient was increased and drag coefficient was reduced, and this was attributed to the creation of a suction region downstream of the fringe. In a similar manner, active oscillations of a trailing edge flap were studied by Simiriotis et al [22]. Their investigation was focused on the wake structure and it was observed that the wake could be reduced in thickness by as much as 10%.…”
Section: Introductionmentioning
confidence: 86%
“…For unsteady CFD simulations Hybrid RANS-LES models are available as well as the k-𝜖 Organized Eddy Simulation model [20,21] which were used for 2D and 3D simulations. The Arbitrary Lagrangian Eulerian (ALE) approach is employed for simulations using moving or deforming grids employed in morphing simulations ( [22,23]). NSMB includes a re-meshing algorithm that is a combination of Volume Spline Interpolation (VSI) [24] and Transfinite Interpolation (TFI).…”
Section: Computational Setup a Nsmb Solver Descriptionmentioning
confidence: 99%